2006
DOI: 10.1111/j.1365-2966.2006.10615.x
|View full text |Cite
|
Sign up to set email alerts
|

The X-ray nuclei of intermediate-redshift radio sources

Abstract: The definitive version is available at www.blackwell-synergy.com. Copyright Blackwell Publishing DOI : 10.1111/j.1365-2966.2006.10615.xWe present a Chandra and XMM-Newton spectral analysis of the nuclei of the radio galaxies and radio-loud quasars from the 3CRR sample in the redshift range 0.1 < z < 0.5. In the range of radio luminosity sampled by these objects, mostly FRIIs, it has been clear for some time that a population of radio galaxies (???low-excitation radio galaxies???) cannot easily participate in m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
259
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(287 citation statements)
references
References 67 publications
27
259
1
Order By: Relevance
“…The second mode of radio activity was first noted by their lack of strong high-excitation narrowline optical excitation expected from the 'quasar' mode (Hine & Longair 1979;Laing et al 1994;Jackson & Rawlings 1997). Moreover, they show no evidence of mid-infrared emission from dusty tori (Whysong & Antonucci 2004;Ogle, Whysong & Antonucci 2006) and no evidence of accretion-related X-ray emission Hardcastle, Evans & Croston 2006). Hardcastle, Evans & Croston (2007) first suggested that this mode, known as the 'lowexcitation', 'radio mode', 'hot mode' or 'jet mode' occurs when hot gas is accreted directly on to the supermassive black hole in a radiatively inefficient manner via advection-dominated accretion flows (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The second mode of radio activity was first noted by their lack of strong high-excitation narrowline optical excitation expected from the 'quasar' mode (Hine & Longair 1979;Laing et al 1994;Jackson & Rawlings 1997). Moreover, they show no evidence of mid-infrared emission from dusty tori (Whysong & Antonucci 2004;Ogle, Whysong & Antonucci 2006) and no evidence of accretion-related X-ray emission Hardcastle, Evans & Croston 2006). Hardcastle, Evans & Croston (2007) first suggested that this mode, known as the 'lowexcitation', 'radio mode', 'hot mode' or 'jet mode' occurs when hot gas is accreted directly on to the supermassive black hole in a radiatively inefficient manner via advection-dominated accretion flows (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, low-redshift GPS galaxies exhibit column densities not systematically lower than high-redshift ones. Hardcastle et al (2006) remark that heavily absorbed nuclei are rather common in narrow-line radio galaxies, whereas they are comparatively rare in Low-Excitation Radio Galaxies (LERG, Laing et al 1994). There are 7 LERGs in our control sample; 5 of them have no column density measurement; the remaining two have column density of 3 × 10 22 cm −2 (3C 123, Hardcastle et al 2006) and 10 23 cm −2 (3C 427.1, Belsole et al 2006).…”
Section: Obscurationmentioning
confidence: 99%
“…Hardcastle et al (2006) remark that heavily absorbed nuclei are rather common in narrow-line radio galaxies, whereas they are comparatively rare in Low-Excitation Radio Galaxies (LERG, Laing et al 1994). There are 7 LERGs in our control sample; 5 of them have no column density measurement; the remaining two have column density of 3 × 10 22 cm −2 (3C 123, Hardcastle et al 2006) and 10 23 cm −2 (3C 427.1, Belsole et al 2006). Taking into account the low number statistics and the uncertainties on the column density upper limits on formally "unobscured" LERGs, the comparison between X-ray obscuration in LERGs and GPSs is inconclusive.…”
Section: Obscurationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, observational evidence is mounting to suggest that this picture does not give a proper description for low-luminosity radioloud AGN (P 1.4 GHz < ∼ 10 25 W Hz −1 ). These objects produce weaker or no emission lines (Hine & Longair 1979;Jackson & Rawlings 1997), lack the dusty torus infrared emission (Ogle et al 2006), and do not produce the accretion related X-ray emission (Hardcastle et al 2006). It has been suggested that there are indeed two very different modes of AGN activity named the "Quasar mode" and the "Radio mode" (Best et al 2005;Hardcastle et al 2007).…”
Section: Introductionmentioning
confidence: 99%